Esensi Single Stroke Pada Awal Pembelajaran Drum - Wismar Sinaga; Agung Dwi Putra (SENDRATASIK UNP, 2021)
Research on this writing to find out that how the technique of single stroke can be said as a basic technique in drumming. the purpose of this study is to see how important rudiment single stroke is too early learning drums. This research is qualitative descriptive research that reveals the current phenomenon. Single stroke technique as a researched object. The location of the research conducted is in the lecture environment of major drum Sendratasik Faculty of Language and Arts, Padang and Drum United Padang Community. Supported by research instruments that are researchers themselves. Techniques in data collection using observation techniques, interview techniques, and documentation techniques. The results of the study were found based on data from pre-field findings obtained through researcher assumptions and field finding data obtained through interview results to informants who are considered to know about single stroke. So the result of this research is rudiment single stroke technique is the basis at the beginning of drum learning because the technique is an easy technique to do than other rudiment techniques. It is also reinforced by the theory of dualism that is the technique of single stroke 2 substances are interrelated, this is about single stroke as the basis of practicing the balance of the left and right hands.